MENDESAIN WAYFINDING JEMBATAN LALUAN MADANI BATAM CENTER - Rico; Ria Sapitri (Puslitabmas Batam Tourism Polytecnic, 2022)
Batam is the largest city in the Riau Islands province, Indonesia. The Batam City area consists of Batam Island, Rempang Island, and Galang Island, and other small islands in the Singapore Strait and Malacca Strait. Batam, Rempang, and Galang islands are connected by the Barelang Bridge. Infrastructure in Batam is also being improved in a better direction. The increase in road capacity has become one of the focuses of the infrastructure projects carried out. The Batam Center area is an area that is a priority for road quality development. Later, the highway in the area will be equipped with green lanes, bicycle lanes, and pedestrians. One of the important infrastructures in Batam is the civil traffic flyover. This is where environmental graphic designers take part, namely as supporters in wayfinding.